IMPLEMENTATION OF MULTISENSORY LEARNING MODELS TO IMPROVE STUDENTS' IMAGINATIVE ABILITIES IN WRITING POETRY - Nazriani; Masri (Universitas Swadaya Gunung Jati, 2025)
The purpose of this research is to implement and test the effectiveness of the multisensory learning model in improving students' imagination skills in writing poetry. The multisensory model is used to stimulate the imagination through sensory stimulation so that it can enrich the creative process of writing poetry. The method used is a mixed method with a quantitative pre-experimental approach (one-group pretest-posttest) and qualitative data support through observation, interviews, and documentation of poetry works. The assessment is carried out based on five main indicators. The results of the t-test analysis showed a value of t = 2.815 with a p-value = 0.013, indicating a significant difference between before and after treatment. These findings show that the multisensory model effectively develops students' imagination in writing poetry. Keywords: multisensory, imagination, writing poetry